A Novel High-Voltage Pulsed-Power Supply Based on Low-Voltage Switch–Capacitor Units - Zabihi, S.; zare, F.; Ledwich, G.; Ghosh, Arindam (Institution of Engineering and Technology ( IET ), 2009)
This paper presents a high-voltage pulsed-power system based on low-voltage switch-capacitor units that are connected to a current source for several applications such as plasma systems. A modified positive buck-boost converter topology is used to utilize the current source concept, and a series of low-voltage switch-capacitor units is connected to the current source in order to provide a high voltage with a high voltage stress (dv/dt) as demanded by the loads. This pulsed-power converter is flexible in terms of energy control because the stored energy in the current source can be adjusted by changing the current magnitude to significantly improve the efficiency of various systems with different requirements. The output-voltage magnitude and stress (dv/dt) can be controlled by a proper selection of components and control algorithm to turn on and off the switching devices.